Meal Vouchers Matter for Academic Attainment: A Community College Field Experiment. (April 2023) - Broton, Katharine M.; Mohebali, Milad; Goldrick-Rab, Sara
Given growing awareness of the high prevalence of food insecurity among college students, higher education leaders are implementing various food interventions on their campuses. However, there is little research on the efficacy and impact of these initiatives. Using data from a field randomized control trial, we find that a relatively modest financial investment in campus meal cards coupled with proactive outreach by an existing campus office improved community college students' academic attainment outcomes. Students who were invited to participate in the meal voucher program attempted and completed more credits during their first year of college and were more likely to graduate in 2 years than otherwise similar peers, indicating that a campus meal program can promote college success.